Vulnerability to suicide ideation: Comparative study between adolescents with and without psychosocial risk - Brás, Marta (2023)
Adolescents are characterized as a risk group for suicide, being the fourth leading cause of death in young people. The main aim was to compare vulnerability to suicidal ideation in a sample of young people with and without psychosocial risk. The total sample consisted of 137 adolescents, aged between 10 and 19 years (M = 14.76; SD = 1.40), and it was composed of two groups—the psychosocial risk group (n = 60) and general population group (n = 77). In both groups, suicidal ideation correlated positively with negative events and negatively with self-esteem and social support satisfaction. When comparing the two groups, the psychosocial risk group presented significantly higher mean values of negative life events (mainly separations/losses and physical and sexual abuse) and significantly lower mean values of satisfaction with social support (particularly with family and social activities). It was also found that, in the psychosocial risk group, negative life events were the only significant predictors of suicidal ideation. This study allowed identifying the role of risk and protective factors in suicidal ideation, according to the psychosocial risk of adolescents. The practical implications of the findings on adolescents’ mental health and the promotion of their well-being are discussed.